2019
DOI: 10.1590/2179-8087.012618
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation Of Climate Change Of Coffee Production Systems In Cundinamarca, Colombia

Abstract: Production systems with woody perennial plants, ideally timber trees, are technologies accepted in carbon (C) projects to mitigate climate change. This research had as purpose the estimation of C storage and fixation in coffee production systems in Cundinamarca, Colombia. Carbon in biomass, necromass and soil were estimated in coffee plantations with three different shade levels (low, medium and high) in three municipalities using IPCC's recommendations. Soil stored 75% of the total C (93.9 to 137.7 Mg C ha-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
4
0
2
Order By: Relevance
“…It is worth noting that resilience is closely related to the other sustainability dimensions, as it refers to system stability over time, in terms of ecosystem services provision, biodiversity conservation, input requirements and socio-economic factors (Reidsma et al 2020). Although the concept of resilience is intrinsically linked to a temporal dimension, some authors propose the use of static measures, such as diversity, as a proxy for resilience (Mijatović et al 2013;Andrade and Zapata 2019). The selection of static indicators, such as diversity, to quantify resilience implies assumptions, for instance, that diversity increases system resilience.…”
Section: Other Categoriesmentioning
confidence: 99%
“…It is worth noting that resilience is closely related to the other sustainability dimensions, as it refers to system stability over time, in terms of ecosystem services provision, biodiversity conservation, input requirements and socio-economic factors (Reidsma et al 2020). Although the concept of resilience is intrinsically linked to a temporal dimension, some authors propose the use of static measures, such as diversity, as a proxy for resilience (Mijatović et al 2013;Andrade and Zapata 2019). The selection of static indicators, such as diversity, to quantify resilience implies assumptions, for instance, that diversity increases system resilience.…”
Section: Other Categoriesmentioning
confidence: 99%
“…Diversos autores han concluido que la fijación de carbono en el SAF es mayor que los monocultivos, ya que la captura de carbono se presenta tanto por los árboles como por los cultivos: (Andrade et al, 2014a;Andrade et al, 2014b;Andrade & Zapata, 2019;Marín et al 2016;Orjuela-Chaves et al, 2014). Con el establecimiento de 600 ha de SAF con cacao en la subcuenca del río Munguidó, se presentaría una fijación de carbono de 1.4 Gg de CO 2 .…”
Section: Discussionunclassified
“…Zaro et al's (2020) study of coffee production in Brazil found that agroforestry stores 47 Mg C ha -1 more in the biomass and soil (up to 70 cm depth) than open coffee systems. Likewise, rates of carbon fixation in plant biomass were found to increase by 5.5-13.9 Mg C ha -1 yr -1 when changing from low to medium and high shade agroforestry in a study of three coffee production systems in Colombia (Andrade and Zapata, 2019). The potential benefits are dependent on the local conditions and management practices.…”
Section: Benefits For Production and Ecosystem Servicesmentioning
confidence: 98%